Analyzing petrographic characteristics and trace element distribution of high-purity quartz deposits from the Peshawar Basin, Pakistan: insights into processing and purification techniques - I. Khan; X. Yang; X. Yang; X. Yang; M. Xia; Z. Hou (European Journal of Mineralogy)
This study examined the potential of quartz vein ore from the Peshawar Basin, Pakistan, as a raw material for producing high-grade, high-purity quartz sand. These samples were purified using a combination of methods including crushing, magnetic separation, ultrasonic cleaning, flotation, high-temperature calcination, water quenching, and acid leaching. Impurities in the quartz vein samples were analyzed through optical microscopy, SEM-CL, Raman spectroscopy, XRD, ICP-OES, and ICP-MS. Petrographic analysis revealed that the main impurities in quartz consisted of fluid inclusions, most of which were concentrated along the microfractures. After purification, the refined quartz sand exhibited a smooth surface with an extremely low concentration of gas–liquid inclusions. The ICP-OES bulk solution analysis of the raw quartz samples showed that the NB-1 SiO2 content is 99.989 wt %, NB-2 99.989 wt %, and NB-3 99.990 wt %. The total impurity content in raw quartz ore was 104.73 µg g−1 for NB-1, 102.25 µg g−1 for NB-2, and 95.01 µg g−1 for NB-3. After purification, the ICP-MS analysis indicates the SiO2 content in processed quartz was 99.999 wt % for NB-1, 99.997 wt % for NB-2, and 99.998 wt % for NB-3, and the total for the 13 impurity elements' content of refined quartz sand was 12.08 µg g−1 for NB-1, 34.57 µg g−1 for NB-2, and 16.79 µg g−1 for NB-3. The main impurity elements, Li and Al, were found in the following concentrations: NB-1 contained 2.06 µg g−1 of Li and 9.16 µg g−1 of Al, NB-2 had 3.23 µg g−1 of Li and 30.15 µg g−1 of Al, and NB-3 showed 2.09 µg g−1 of Li and 13.68 µg g−1 of Al. These impurities can be further reduced using more advanced techniques. Based on these results, these purified quartz sands are suitable for producing high-purity quartz products (4N7 to 4N9) that meet the standard requirements for crucible preparation for industrial applications. Therefore, these quartz vein ores are considered potential resources for high-purity quartz (HPQ).